2021
DOI: 10.1093/ckj/sfab218
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chronic kidney disease–associated pruritus and health-related quality of life: a systematic review

Abstract: Background Chronic kidney disease associated pruritus (CKD-aP) is a common and burdensome condition for end-stage kidney disease (ESKD) patients, especially those receiving haemodialysis. High quality evidence of the relationship between CKD-aP and health-related quality of life (HRQoL) can therefore inform clinicians and policy makers about treatment choice and reimbursement decisions. Methods Systematic Literature Review an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Patients and healthcare professionals have prioritised other measures of HRQoL in people on dialysis [ 32 ], and other randomised controlled trials (RCTs) have shown the relative insensitivity of the EQ-5D instrument in this patient group [ 33 ]. A recent systematic review of the impact of CKD-aP on HRQoL reported that RCTs that showed improvements in CKD-aP severity were associated with clinically meaningful improvements in HRQoL [ 34 ]. It was also noted that disease-specific HRQoL instruments reported greater changes with reduced CKD-aP severity than generic instruments [ 34 ], and this has been shown in other skin conditions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients and healthcare professionals have prioritised other measures of HRQoL in people on dialysis [ 32 ], and other randomised controlled trials (RCTs) have shown the relative insensitivity of the EQ-5D instrument in this patient group [ 33 ]. A recent systematic review of the impact of CKD-aP on HRQoL reported that RCTs that showed improvements in CKD-aP severity were associated with clinically meaningful improvements in HRQoL [ 34 ]. It was also noted that disease-specific HRQoL instruments reported greater changes with reduced CKD-aP severity than generic instruments [ 34 ], and this has been shown in other skin conditions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the impact of CKD-aP on HRQoL reported that RCTs that showed improvements in CKD-aP severity were associated with clinically meaningful improvements in HRQoL [ 34 ]. It was also noted that disease-specific HRQoL instruments reported greater changes with reduced CKD-aP severity than generic instruments [ 34 ], and this has been shown in other skin conditions [ 35 ]. This recognised lack of sensitivity led to the development of the disease-specific ‘bolt-on’ module – EQ-PSO [ 24 ]; this added ‘skin irritation’ and ‘self-confidence’, which were observed to improve in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews and these trials have shown that disease-specific HRQoL measures are sensitive to changes in pruritus severity in CKD-aP, but the degree to which EQ-5D improves with lessening CKD-aP severity within individuals remains unobserved ( 5 ): open-label trial data for the use of difelikefalin for CKD-aP that also included EQ-5D-5L is available for comparison ( 31 ): participants being treated with difelikefalin had a clinically meaningful change in EQ-5D utility of 0.04, and 73.7% of patients on difelikefalin improved their WI-NRS by ≥3 points (comparable to 1 Verbal Rating Scale level). Due to the nature of the trial’s reported data and the cross-sectional study design twe are unable to confirm if changes in CKD-aP severity in response to therapies yield similar improvements in HRQoL as those estimated from our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…of the pruritus is associated with depression, poor sleep quality, increased mortality and reduced health-related quality of life (HRQoL) (3)(4)(5). Patients and clinicians have repeatedly prioritized the treatment of CKD-aP (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation